Surgical Orthodontic Management of Impacted Maxillary Teeth in the Esthetic Zone - Chhean, Sok-Chenh (Archive of Orofacial Data Science, 2025)
AIM: This study aimed to investigate differences in aesthetic aspects of gingival conditions, periodontal pocket depths, root lengths, and crown lengths of impacted maxillary central incisors and canines treated with the closed-eruption management technique. METHODS: This review focused on the closed-eruption approach (CEA) for impacted maxillary central incisors and canines located on the vestibular or palatal sides. A comprehensive literature search was conducted using Electronic PubMed, employing keywords such as "closed-eruption approach", "impacted maxillary incisor", "impacted maxillary canine", and "surgical orthodontic retraction". Additional journals were consulted to gather further information. Out of 45 identified articles, 10 publications from 2007 to 2015 met the inclusion criteria. RESULTS: After analyzing the 10 eligible articles, results showed detailed descriptions of gingival conditions (e.g., OGH, KT, GC, GM), periodontal pocket depths (PPD), root lengths (RL), and crown lengths (CL) of impacted central incisors and canines following CEA treatment. Notably, distinct outcomes emerged between impacted maxillary incisors (IMIs) and impacted maxillary canines (IMCs). CONCLUSION: Treating impacted teeth in the aesthetic zone of the maxillary region requires thorough comprehension of surgical procedures. Our findings suggest that the closed-eruption approach (CEA) is a reliable technique yielding favorable outcomes for gingival tissues, PPD, RL, and CL upon completion of treatment.